Mesoporous polymeric microspheres with high affinity for phosphorylated biomolecules. (23rd April 2018) - Shinde, Sudhirkumar; Selvalatchmanan, Jayashree; Incel, Anil; Akhoundian, Maedeh; Bendt, Anne K.; Torta, Federico
Abstract : Bis-imidazolium functionalized mesoporous microspheres selectively extract phosphorylated peptides/lipids from biofluids. Abstract : Phosphate plays a central role in the environment and in biology. This has led to the demand for a specific phosphate receptor that can be used to sense, enrich or separate phosphate and phosphorylated molecules from complex mixtures. Here, we report an approach for the production of phospho-affinity porous beads with controllable size and pore structure leading to significantly improved chromatographic properties. The beads were prepared by polymerization of bis-imidazolium based host monomer and crosslinker inside the pores of macroporous silica beads that post-etching resulted in mesoporous polymer replicas. The silica precursor, silica–polymer composite and porous polymer replica were characterized by using SEM, IR spectroscopy, optical microscopy and thermogravimetric analysis. Bis-imidazolium functionalized materials were capable of binding and enriching the signaling lipid sphingosine-1-phosphate from plasma samples. Moreover, these engineered materials combined with artificial receptors can recognize phosphorylated amino acids/peptides and are applicable to selective recognition of a broad class of phosphorylated biomolecules.